Kiprah Remaja Putri Dalam Sekaa Gong Istri Dharma Laksana (Penelitian Di Kelurahan Banjar Tengah Kecamatan Negara Kabupaten Jembrana) - Dyanesca Sicillia Kumara, Nyoman Ayu; Arjani, Ni Luh (Humanis; Volume 16. No. 3. September 2016, 2016)
Art is the one of the culture in bali that really fast to grow. In this globalisation, modern art has many teenagers liker than old culture. It's really difficult to find some of them who like the old culture. One of the example of the culture that doesn't have many likers among the teenagers is gong kebyar. In this experimental, writers will explain about the interesting of some teenagers about the old culture, gong kebyar. Such as : 1. Why the girls are interested to join the sekaa gong Dharma Laksana ? 2.what the personal impact of joining sekaa gong Dharma Laksana ? 3.what the people think of the girls that do the old culture (gong kebyar) in the sekaa Dharma Laksana? The theory that writer use in this experimental is three social motif From David Mc.Clelland and the Feminims Posmodern theory from Linda Nicholson.the main concept in this experimental is about the girls that still doing the old culture in this globalism. Writers use the cualitative methods.